BETWEEN INNOVATION AND CHALLENGES: UTILIZATION OF BLOCKCHAIN AND CLOUD PLATFORMS IN THE TRANSFORMATION OF BANKING SERVICES IN THE DIGITAL ERA - Aripin, Zaenal; Paramarta, Vip; Kosasih (Organisasi Kreatif Indonesia Emas, 2024)
Banking in the digital era is increasingly pressured to adopt new technologies to update and improve their services. Two prominent technologies in the transformation of banking services are blockchain and cloud computing. Blockchain technology offers security and transparency, while cloud computing provides flexibility and efficiency in IT infrastructure. This research aims to explore the innovations and challenges associated with the utilization of blockchain and cloud technologies in the transformation of banking services in the digital era. We seek to understand how banks implement these technologies and identify factors influencing the success or failure of implementation. The research method used is descriptive qualitative. Data were collected through literature studies from journals, articles, and books relevant to this research topic. Analysis was conducted to identify trends, challenges, and benefits of using blockchain and cloud technologies in banking services. The results show that the utilization of blockchain and cloud technologies has brought significant changes in banking services, including improved security, operational efficiency, and financial inclusion. However, banks also face several challenges, including technical complexity, initial investment costs, and regulatory compliance.